EKOFEMINISME DAN PERAN PEREMPUAN DALAM LINGKUNGAN - Pudji Astuti, Tri Marhaeni (Indonesian Journal of Conservation, 2012)
Ecofeminism is a move emerges among women all over the world from various professions as the result of the unfairness towards women who are always being a myth of nature. This paper suggests a variety of examples of womens role in the environment in various countries. Discussion about the environment as well as the implications associated with ecofeminism high feminist consciousness among women scientists in universities in the world. The feminist awareness upon exploitations to the nature brings them to the action of saving the environment to create an eco-friendly and women-friendly way of living. The key of this case is involving and giving empathy to women for their role in the environment. Therefore it is urgent to understand the local wisdom as a reference by using the deconstruction of local wisdom to create the reconstruction of a new environmentally friendly local wisdom.ÃÂ Ekofeminisme merupakan sebuah gerakan yang muncul di kalangan perempuan di berbagai belahan dunia dari berbagai profesi sebagai akibat adanya ketidak adilan terhadap perempuan yang selalu dimitoskan dengan alam. Tulisan ini mengemukakan berbagai contoh peran perempuan dalam lingkungan hidup di berbagai Negara. Pembahasan tentang lingkungan juga terkait dengan ekofeminisme sebagai implikasi kesadaran feminis yang tinggi di kalangan ilmuwan perempuan di perguruan tinggi di berbgagai belahan dunia. Kesadaran para perempuan feminis terhadap eksploitasi alam membuat mereka bangkit berperan dalam penyelamatan lingkungan hidup sehingga tercipta kehidupan yang eco-friendly dan Womenfriendly. Kunci dari hal itu adalah melibatkan dan empati terhadap perempuan dalam perannya dalam lingkungan hidup. Oleh karenanya perlu memahami kearifan lokal sebagai sebuah acuan dengan dekonstruksikearifan lokal agar muncul rekonstruksi kearifan lokal baru yang ramah lingkungan.